Non-similar modeling and numerical simulations of microploar hybrid nanofluid adjacent to isothermal sphere - Abbasi A.; Farooq W.; Gul M.; Gupta Manish; Abduvalieva Dilsora; Asmat Farwa; AlQahtani Salman A. (Open Physics, 2023)
In today’s era of rapid technological development, there is an increasing requirement for high-functioning investiture solutions, working liquids and materials that can satisfy the benchmarks of energy efficacy. Specifically, within the domain of heat transference-based industries, an essential challenge is to fabricate a cooling medium that can effectually cope with dissipation of substantial heat flux engendered by high-energy utilizations. At present, nanoliquids are extensively deliberated as some of the most promising aspirants for such effectual cooling mediums. The current investigation features hybrid nanoliquid flow adjacent to magnetized non-isothermal incompressible sphere. Rheological expressions representing micropolar liquid are accounted for flow formulation. The rheological analysis is developed using the boundary-layer concept. Buoyancy impact is accounted for heat transference analysis. Nanoparticles with distinct shapes are considered. The developed nonlinear systems are computed numerically and non-similar simulations are performed.